Evaluation of a Standardized Program for Training Practicing Anesthesiologists in Ultrasound‐Guided Regional Anesthesia Skills. (18th September 2015) - Mariano, Edward R.; Harrison, T. Kyle; Kim, T. Edward; Kan, Jack; Shum, Cynthia; Gaba, David M.; Ganaway, Toni; Kou, Alex; Udani, Ankeet D.; Howard, Steven K.
Abstract : Objectives: Practicing anesthesiologists have generally not received formal training in ultrasound‐guided perineural catheter insertion. We designed this study to determine the efficacy of a standardized teaching program in this population. Methods: Anesthesiologists in practice for 10 years or more were recruited and enrolled to participate in a 1‐day program: lectures and live‐model ultrasound scanning (morning) and faculty‐led iterative practice and mannequin‐based simulation (afternoon). Participants were assessed and recorded while performing ultrasound‐guided perineural catheter insertion at baseline, at midday (interval), and after the program (final). Videos were scored by 2 blinded reviewers using a composite tool and global rating scale. Participants were surveyed every 3 months for 1 year to report the number of procedures, efficacy of teaching methods, and implementation obstacles. Results: Thirty‐two participants were enrolled and completed the program; 31 of 32 (97%) completed the 1‐year follow‐up. Final scores [median (10th–90th percentiles)] were 21.5 (14.5–28.0) of 30 points compared to 14.0 (9.0–20.0) at interval ( P < .001 versus final) and 12.0 (8.5–17.5) at baseline ( P < .001 versus final), with no difference between interval and baseline. The global rating scale showed an identical pattern. Twelve of 26 participants without previous experience performed at least 1 perineural catheter insertion after training ( P < .001). However, there were no differences in the monthly average number of procedures or complications after the course when compared to baseline. Conclusions: Practicing anesthesiologists without previous training in ultrasound‐guided regional anesthesia can acquire perineural catheter insertion skills after a 1‐day standardized course, but changing clinical practice remains a challenge.